Link of Helicobacter Pylori (H. pylori) to Overweight Patients and Patients with Obesity in two Obesity Centers-Sulaimani Governorate-Kurdistan-Iraq, Prospective Case Study Series - Ahmed, Hiwa Omer; Muhialdeen, Aso (Technium BioChemMed, 2021)
Abstract: Background The prevalence of overweight and obesity worldwide was estimated, claiming that one-third of adult individuals suffering from overweight or obesity; and in some regions, the prevalence of adults' obesity exceeded 50% Objectives: To find the incidence of Helicobacter pylori infection in overweight patients and patients with obesity, visiting two bariatric centers in Sulaimani governorate. Patients and methods: A prospective case series study including 60 patients with overweight or obesity was conducted in Sulaimani Teaching Hospital for seven months from October 1st, 2020, to April 30th, 2021. Results: From a total of (60) patients (6) males, (6) females were overweight, while (18) males, (30) females were obese. Serology for H. pylori done for all the patients was positive in (41/60=68%), while stool was positive just in (22/59=37%). Conclusion: Seroprevalence of anti-H. Pylori in the patients showed a possible relationship between infection with H. pylori and gaining weight. However, serology tests may be undependable, and gastric mucosal biopsy may be more accurate in testing for H. pylori, especially in bariatric patients before and after the operations.